A Task Alignment Framework for Low Cost Distributed Systems targeting Synchronized Monitoring and Control. Issue 24 (2019) - Li, Fangyuan; Wan, Yanni; Qin, Jiahu
Abstract: In many areas such as sensor networks and smart grid, synchronized monitoring and control are usually required to enable the functionalities of the overall system. Clock synchronization is treated as a precondition to satisfy the synchronized monitoring and control. However, clock synchronization alone is not sufficient to meet these requirements, especially for the situations where low cost distributed embedded systems are involved. Latency and hardware resources are typical impact factors to the synchronization. This paper focuses on proposing a task alignment framework for low cost distributed systems relying only on a minimal set of hardware components. The system architecture and hardware components are presented first. Then the paper presents a task alignment algorithm under the proposed framework. The issues such as inevitable communication delays and execution delays are also addressed. Finally, simulation results verify the effectiveness of the proposed framework.